Pemberdayaan dalam Meningkatkan Kesejahteraan Petani Bawang Merah di Kecamatan Medan Marelan - Nurliana Harahap; Yusra Muharami Lestari; Ameilia Zuliyanti Siregar (Jurnal Penyuluhan, 2023)
Welfare is the hope of everyone, including farmers, that various efforts are made so that the income and welfare of farmers can increase. One of them is through empowerment so that farmers can produce independence both economically, managerially, and socially. This study aims to find out how the implementation of the empowerment of shallot farmers in improving welfare and identify supporting and inhibiting factors in empowering shallot farmers in Medan Marelan District, Medan City. This study uses a qualitative approach. Data collection techniques are carried out through observation, interviews, and documentation. Data validation techniques used in this study are source triangulation and method triangulation. The data analysis technique used in this study is qualitative data analysis techniques, namely data collection, data reduction, data presentation, and ng concluding/verification. The results of the study show that the forms of empowerment carried out by shallot farmers in improving welfare are carried out through regular meetings, self-help, and mutual cooperation, capital, provision of shallot production facilities, as well as the support and role of stakeholders. Supporting factors for increasing the welfare of farmers are the provision of production facilities by the government, vegetable commodities as support, training, and comparative studies. While the inhibiting factors are reduced land area and not yet optimal farmer institutions.